Kajian Yasinan Mingguan dalam Membina Karakter Masyarakat Pada Masa Covid-19 di Perumahan Lebak Kinasih Purwakarta - Imam Tabroni; Rini Purnamasari (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
This Community Service article aims to change the bad character so that it becomes good for the community in Lebak Kinasih Housing Purwakarta. The service method uses a mix method approach with a Participatory Action Research (PAR) design. First, conducting observations and interviews to fill out a questionnaire related to the character of the community by presenting descriptive statistical data. The second step is analyzing the problem and followed by the next step systematically by taking actions in the form of a yasinan study every Friday night by observing changes in the character of the community. A series of actions produces a step-by-step change. Changes in character begin with a good understanding of social life, then a strong desire to change behavior, and finally awareness of good deeds that are carried out spontaneously between individuals. Through weekly yasinan studies, it can be found that effective and efficient actions change the character of the community through the stages of understanding religious values ​​(cognitive), social attitudes (attitude), the spirit of doing good (motivation), daily actions (behaviors), and certain skills (skills).